2016
DOI: 10.1016/j.asjsur.2015.11.003
|View full text |Cite
|
Sign up to set email alerts
|

Surgical complications after simultaneous pancreas–kidney transplantation: A single-center experience

Abstract: We conclude that the high rate of surgical complications is a major obstacle to widespread application of pancreas transplantation; early recognition and appropriate treatment of graft-related complications is fundamental for graft survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 7 publications
0
18
0
1
Order By: Relevance
“…In our daily practice, we have observed that patients who have undergone SPKT, even when they have experienced major postoperative complications , and, in some cases, lost one or both grafts, still wish to be put on the waiting list for re‐transplantation. We have questioned, for example, what factors would lead to a patient's desire to be put on the waiting list again, despite the great psychological and physical suffering involved, including the risk of serious complications and even possible death given the initial unsuccessful transplant.…”
Section: Discussionmentioning
confidence: 99%
“…In our daily practice, we have observed that patients who have undergone SPKT, even when they have experienced major postoperative complications , and, in some cases, lost one or both grafts, still wish to be put on the waiting list for re‐transplantation. We have questioned, for example, what factors would lead to a patient's desire to be put on the waiting list again, despite the great psychological and physical suffering involved, including the risk of serious complications and even possible death given the initial unsuccessful transplant.…”
Section: Discussionmentioning
confidence: 99%
“…Generally the pancreas and kidney are transplanted with an intraperitoneal approach into contralateral iliac fossae . There is evidence that of the routinely performed solid organ transplants, pancreas transplantation has the highest rate of complications . This is likely a result of the exocrine secretions of the pancreas as well as its low microcirculatory blood flow …”
Section: Discussionmentioning
confidence: 99%
“…Pancreas transplantation is known to confer high patient morbidity and mortality, often leading to complications with a prolonged hospital stay. The median length of stay after transplant varies by centre but has been reported in the range of 8-27 days [14,15], with some studies putting the postoperative complication rate at close to 40% with reoperation rates exceeding 30% [16,17]. The patients themselves are also known to be high risk, with virtually all patients have diabetes mellitus, and many of these patients have concomitant cardiovascular or renal disease.…”
Section: Why Is An Eras Pathway So Important For Pancreatic Transplantation?mentioning
confidence: 99%